Dandelion Seed Extract Affects Tumor Progression and Enhances the Sensitivity of Cisplatin in Esophageal Squamous Cell Carcinoma - Li, Yuxi; Deng, Yuying; Zhang, Xiuli; Fu, Han; Han, Xue; Guo, Wenqing; Zhao, Wei; Zhao, Xuening; Yu, Chunxue; Li, Hui; Lei, Kaijian; Wang, Tianxiao (Frontiers in Pharmacology, 2022)
Like dandelion, dandelion seed also have anti-inflammatory activity. Therefore, in this article, we intend to explore the anti-cancer availability of aqueous dandelion seed extract (DSE) in esophageal squamous cell carcinoma (ESCC). Firstly, the effects of DSE on cell proliferation, apoptosis, migration, invasion and angiogenesis were investigated. Then to explore the mechanism of DSE against ESCC, the levels of proliferation-associated proteins (PI3K, Akt and pAkt), apoptosis-associated proteins (survivin, Bcl-2, Bax, caspase3 and caspase9), metastasis-associated proteins (MMP2, MMP9, VEGF) and EMT progression-associated proteins (Snail, E-cadherin and Vimentin) were analyzed. Next, we further explored the effect of DSE on the sensitivity of cisplatin (DDP) in ESCC cells and investigated the effect of DSE combined with DDP on DNA damage repair-associated proteins (MSH2 ,MLH1 and ERCC1) and drug resistant target protein STAT3. The results indicated that DSE selectively inhibited cell growth, proliferation, migration, invasion, angiogenesis and induced cell apoptosis in ESCC cells. It was observed the decreased PI3K, Akt and pAkt proteins levels in KYSE450 and Eca109 cells administrated with DSE. The data also showed that the application of DSE decreased the level of survivin and the ratio of Bcl-2/Bax, while increased the levels of caspase3 and caspase9. We also observed that DSE significantly decreased the levels of MMP2, MMP9 and VEGF proteins and inhibited the EMT progression in KYSE450 and Eca109 cells. In addition, survivin plays a critical role in DSE against ESCC followed with the application of survivin inhibitor YM155 impairing the inhibitory abilities of DSE in ESCC cells. Meanwhile, it was observed that DSE enhances the sensitivity of DDP to human ESCC cells via promoting DNA damage and inhibiting phosphorylation of STAT3. Therefore, DSE may affect ESCC progression and enhance the sensitivity of cisplatin, and consequently become an effective anti-cancer option for human ESCC treatment.